2018
DOI: 10.1136/heartjnl-2017-312869
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in the contribution of Chagas cardiomyopathy to mortality among patients with heart failure

Abstract: Although the absolute death rates decreased over time in the ChC and NChC groups, the PAR of ChC for mortality increased among patients with HF, driven by increases in the HR associated with ChC. Our results highlight the need for additional efforts aiming to prevent and treat ChC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
2
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 29 publications
1
12
2
8
Order By: Relevance
“…[5][6][7][8] Indeed, a recent study from Brazil concluded that the population attributable mortality risk from CCC increased between 2002/2004 and 2012/2014. 9 Future trials should consider recruiting larger numbers of patients with CCC to allow adequately powered subgroup analysis and even trials specifically in CCC would be justified, given the magnitude of this problem. Until that time, patients with CCC should be treated empirically with therapies recommended by guidelines, on the assumption that treatments for patients with reduced ejection fraction are effective, irrespective of aetiology of HF.…”
mentioning
confidence: 99%
“…[5][6][7][8] Indeed, a recent study from Brazil concluded that the population attributable mortality risk from CCC increased between 2002/2004 and 2012/2014. 9 Future trials should consider recruiting larger numbers of patients with CCC to allow adequately powered subgroup analysis and even trials specifically in CCC would be justified, given the magnitude of this problem. Until that time, patients with CCC should be treated empirically with therapies recommended by guidelines, on the assumption that treatments for patients with reduced ejection fraction are effective, irrespective of aetiology of HF.…”
mentioning
confidence: 99%
“…A média da idade na casuística (57,7 anos; desvio-padrão 13,1) foi de pacientes com idade inferior a 65 anos (71%), à semelhança de outros estudos, que verificaram médias de idade entre 51,7 anos (desvio-padrão 8,3) e 59 anos (desvio-padrão 14 anos) (Bestetti et al, 1997;Freitas et al, 2005;Silva et al, 2007;Nadruz et al, 2018), embora haja casuísticas publicadas com média de idade superior a 61 anos (Roger et al, 2004;Rohde et al, 2005;Moutinho et al, 2008;Shah et al, 2017) e outra com média de idade de 48 anos desviopadrão 12 anos (Nunes et al, 2008).…”
Section: Idadeunclassified
“…A frequência de homens em relação a mulheres predominou (64%) na casuística, assim como em outros estudos (Likoff et al, 1987;Bestetti et al, 1997;Lewis et al, 2003;Freitas et al, 2005;Rassi et al, 2006;Ahmed et al, 2006a;Theodoropoulos et al, 2007;Nunes et al, 2008;Marcula et al, 2011;Carlo et al, 2014;Gheorghiade et al, 2013;Abdul-Rahim et al, 2016;Nadruz et al, 2018).…”
Section: Sexounclassified
See 2 more Smart Citations